PWE-134 Single incision vs conventional laparoscopic cholecystectomy: a meta-analysis and systematic review of randomised controlled trials. (28th May 2012) - Sajid, M; Ladwa, N; Baig, M K; Singh, K; Sayegh, M
Abstract : Introduction: To systematically analyse the randomised trials comparing single incision laparoscopic cholecystectomy (SILC) vs conventional laparoscopic cholecystectomy (CLC). Methods: The meta-analysis was conducted according to the Quality of Reporting of Meta-analysis (QUORUM) standards. Standard electronic databases were searched to retrieve relevant randomised trials comparing SILC vs CLC and analysed systematically using RevMan®. Summated outcomes were expressed as RR and standardised mean difference (SMD). Results: Eleven randomised, controlled trials encompassing 859 patients were retrieved for the electronic databases. In the random effects model, post-operative pain, post-operative complications, length of hospital stay, cosmesis score, conversion rate, additional ports insertion rate and time for return to normal activities were statistically comparable between two techniques of cholecystectomy. The SILC is associated with longer operative time. However, there was significant heterogeneity among included trials. Conclusion: SILC does not offer any significant advantage over CLC to treat benign gallbladder disorders. CLC may assiduously be used for this purpose. Competing interests: None declared.